Metachromatic Leukodystrophy - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 1990)
A ten year old girl with metachromatic leukodystrophy in whom neurophysiologic function and sulfatide metabolism had improved after she received a bone marrow transplant five years before is reported from the Bone Marrow Transplantation Program, Department of Pediatrics and Division of Pediatric Neurology, University of Minnesota, MN and other centers.